Bernie and David Araiza Wedding at St. John's Cathedral - Watkins, Howard::::::::: (1981)
Christine Watkins in black jacket, Adam Watkins wearing long sleeve tuxedo looking shirt, Joe Floyd Asher in three-piece brown polyester suit